BATU NA PIR SITINJAK AS A CULTURAL TEXT: INTERPRETATIONS OF RITUAL AND FORM IN BATAK TOBA TRADITIONAL ART - Marfenas Marolop Sihombing; Ikhwanuddin Nasution; Agus Priyatno (Universitas Negeri Medan, 2026)
Batu Na Pir Sitinjak is a stone burial monument of the Batak Toba people that serves as a profound medium for cultural, spiritual, and social expression. This study aims to examine Batu Na Pir Sitinjak as a